Access 3 project protocol: young people and health system navigation in the digital age: a multifaceted, mixed methods study. Issue 8 (7th August 2017) - Kang, Melissa; Robards, Fiona; Sanci, Lena; Steinbeck, Katharine; Jan, Stephen; Hawke, Catherine; Kong, Marlene; Usherwood, Tim
Abstract : Background: The integration of digital technology into everyday lives of young people has become widespread. It is not known whether and how technology influences barriers and facilitators to healthcare, and whether and how young people navigate between face-to-face and virtual healthcare. To provide new knowledge essential to policy and practice, we designed a study that would explore health system access and navigation in the digital age. The study objectives are to: (1) describe experiences of young people accessing and navigating the health system in New South Wales (NSW), Australia; (2) identify barriers and facilitators to healthcare for young people and how these vary between groups; (3) describe health system inefficiencies, particularly for young people who are marginalised; (4) provide policy-relevant knowledge translation of the research data. Methods and analysis: This mixed methods study has four parts, including: (1) a cross-sectional survey of young people (12–24 years) residing in NSW, Australia; (2) a longitudinal, qualitative study of a subsample of marginalised young people (defined as young people who: identify as Aboriginal and/or Torres Strait Islander; are experiencing homelessness; identify as sexuality and/or gender diverse; are of refugee or vulnerable migrant background; and/or live in rural or remote NSW); (3) interviews with professionals; (4) a knowledge translation forum. Ethics and dissemination: Ethics approvals were sought and granted. Data collection commenced in March 2016 and will continue until June 2017. This study will gather practice and policy-relevant intelligence about contemporary experiences of young people and health services, with a unique focus on five different groups of marginalised young people, documenting their experiences over time. Access 3 will explore navigation around all levels of the health system, determine whether digital technology is integrated into this, and if so how, and will translate findings into policy-relevant recommendations.